Design optimization and test of the novel FeTu 'compander', utilising organic fluids within a closed cycle for HVACR applications. Issue 1 (September 2021) - Subert, J; Fenton, J P; Hinchliffe, K; Arbon, I M
Abstract: HVACR performance is influenced by the efficiency of the compression and expansion process. The ability to operate oil-free; with non-toxic, inert, natural working fluids such as air or CO2 holds high environmental value. This paper presents data of the FeTu™ compander operating in a closed cycle, for means of heating and cooling. A novel system, where compression and expansion is a continuous and simultaneous process; inherently regenerating energy to assist the compression process by expanding within a positive displacement chamber. This study documents the oil-free performance with organic working fluids pertaining to HVACR applications. Commercial 1D modelling software; GTSuite (GTS) is used to optimise cooling capacity (Q) and Coefficient of Performance (CoP). Different volume ratios (VR), pre-charge pressures, temperature inputs (ΔT) and running speeds are analysed. A multi-faceted test rig is built to compare and validate all performance data against the GTS fluid model which, once calibrated, can then be used with a high degree of certainty in predicting the performance of other applications and ΔTs. Increasing the system pre-charge pressure has a proportional impact on capacity, so this phenomenon is tested to consider the conflicting impacts of higher pressure against increased viscosity, with respect to volumetric efficiency. The CoP of the system ranges from 1 to 5 across typical HVACR ΔTs. Low VR offers highest CoP but lowest Q, so the optimal trade-off is explored. The strengths & weaknesses are then comparatively documented against incumbent vapour cycle systems.